Causal agents of Fusarium head blight of durum wheat (Triticum durum Desf.) in central Italy and their in vitro biosynthesis of secondary metabolites - Beccari, G.; Colasante, V.; Tini, F.; Senatore, M.; Prodi, A.; Sulyok, M.; Covarelli, Lorenzo (N R C Research Press, 2018)
Durum wheat samples harvested in central Italy (Umbria) were analyzed to: evaluate the occurrence of the fungal community in the grains, molecularly identify the Fusarium spp. which are part of the Fusarium head blight (FHB) complex and characterize the in vitro secondary metabolite profiles of a subset of Fusarium strains. The Fusarium genus was one of the main components of the durum wheat fungal community. The FHB complex was composed of eight species: Fusarium avenaceum (61%), F. graminearum (22%), F. poae (9%), F. culmorum (4%), F. proliferatum (2%), F. sporotrichioides (1%), F. sambucinum (0.5%) and F. langsethiae (0.5%). F. graminearum population was mainly composed of the 15-acetyldeoxynivalenol chemotype, while, F. culmorum population was composed of the 3-acetyldeoxynivalenol chemotype. In vitro characterization of secondary metabolite biosynthesis was conducted for a wide spectrum of substances, showing the mycotoxigenic potential of the species complex. F. avenaceum strains were characterized by high enniantin and moniliformin production. F. graminearum strains were in prevalence deoxynivalenol producers. F. poae strains were characterized by a high biosynthesis of beauvericin like the F. sporotrichioides strain which was also found to be a high T-2/HT-2 toxins producer. Production of aurofusarin, butenolide, gibepyrone D, fusarin C, apicidin was also reported for the analyzed strains.